2012
DOI: 10.1002/marc.201200531
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Crystallization Kinetics on Microstructure and Charge Transport of Polythiophenes

Abstract: We have examined the effects of crystallization kinetics of poly(3-hexylthiophene) and poly[2,5-bis(3-hexadecylthiophen-2-yl)thieno(3,2-b)thiophene] on microstructure and charge transport. Rapid crystallization increases the density of tie molecules in polythiophenes. As a consequence, ordered regions are better connected resulting in higher charge carrier mobilities. Our results suggest that controlling the crystallization kinetics might be an important factor for maximizing the charge mobility in semicrystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 31 publications
3
46
0
Order By: Relevance
“…We speculate that PAEKs and other semicrystalline rigid polymers with larger crystallites formed at low supercoolings (nucleation limited) exhibit higher strength and lower ductility compared to specimens with smaller crystallites formed at high supercoolings (diffusion limited) . A semicrystalline morphology with smaller crystals formed under diffusion‐limited conditions could lead to less brittle materials due to greater tie chain densities …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate that PAEKs and other semicrystalline rigid polymers with larger crystallites formed at low supercoolings (nucleation limited) exhibit higher strength and lower ductility compared to specimens with smaller crystallites formed at high supercoolings (diffusion limited) . A semicrystalline morphology with smaller crystals formed under diffusion‐limited conditions could lead to less brittle materials due to greater tie chain densities …”
Section: Resultsmentioning
confidence: 99%
“…47,48 A semicrystalline morphology with smaller crystals formed under diffusion-limited conditions could lead to less brittle materials due to greater tie chain densities. 49 Although PEEK retains a higher strength after 72 h of steam exposure, the material becomes soft at elevated temperatures. Supporting Information Figure S4 shows that PEEK deforms significantly at 350 C, whereas XL-PEKK(75/25) does not.…”
Section: Flexural Propertiesmentioning
confidence: 99%
“…The formation of such physical connections depends on the polymer chain contour length, the polymer chain persistence length, and the characteristic spacing between neighboring ordered regions . For such purposes, polymers with high MWs and high crystallinity are needed. And, as described above, polymers with rigid coplanar backbones have higher persistence length, which should in turn also facilitate the formation of tie chains …”
Section: Opportunities For Improving Charge Transportmentioning
confidence: 99%
“…Moreover, Gomez's group increased the connectivity between ordered regions of polythiophene by modulating the crystallization kinetics of polythiophene through thermal treatment. They found that the faster crystallization rate led to more tie chains between crystalline regions and consequently higher charge mobilities in organic thin-film transistors [19].…”
Section: Introductionmentioning
confidence: 99%